Long-term exposure to electric fields. A cross-sectional epidemiologic investigation of occupationally exposed workers in high-voltage substations. - Knave, Bengt; Gamberale, Francesco; Bergström, Sven; Birke, Elisabeth; Iregren, Anders; Kolmodin-Hedman, Birgitta; Wennberg, Arne (Scandinavian Journal of Work, Environment & Health, 1979)
In the present epidemiologic study, 53 workers with a long-term (more than five years) exposure to the electric field of 400 kV substations were examined and compared with a matched reference group of 53 nonexposed workers from the same power companies. Matching variables included age, geographic location and employment time. The aim of the study was to investigate the possibility of persistent, chronic health effects in the exposed group as a consequence of exposure. The investigation indluded the nervous system (neurasthenic symptoms, psychological tests, electroencephalography), the cardiovascular system (symptoms, blood pressure, electrocardiography), and the blood (hemoglobin, red blood cells, reticulocytes, white blood cells including differential count, thrombocytes, sedimentation rate). Fertility was also assessed. The results showed no differences between the exposed and reference groups as a consequence of the long-term exposure to the electric fields. The groups differed, however, in that the exposed group had (a) consistently better results on the psychological performance tests, (b) a fewer number of children, especially boys, and (c) somewhat higher education. The differences in test results were due to the higher education among the exposed. The difference in number of children was also thought to be related to factors other than exposure since it was found to be present already 10–15 years before the work in 400 kV substations began.
Keywords: blood; cardiovascular system; cross-sectional epidemiologic investigation; cross-sectional investigation; electric fields; electromagnetic fields; epidemiologic investigation; epidemiologic study; fertility; health examination; high-voltage substation; long-term exposure; nervous system; occupational exposure; substation worker; worker